2022
DOI: 10.3389/ffgc.2022.976902
|View full text |Cite
|
Sign up to set email alerts
|

Phyto-ecological analysis of Phytolacca acinosa Roxb. assemblages in Kashmir Himalaya, India

Abstract: Phyto-ecological studies are essential in understanding community structure, organization and their response to changes in other environmental factors. In this study we analyzed the phytosociological and soil characteristics of Phytolacca acinosa communities and their correlation. 110 quadrats were laid across ten randomly selected sites in Kashmir Himalaya, India. Soil analysis was done using standard protocols. Overall, 161 species were recorded, belonging to 128 genera and 49 families. The species richness … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 63 publications
0
7
0
Order By: Relevance
“…As observed from the IVI analysis, P. austroarabica had the highest importance value (107.28) as compared with other parasitic species. Magray et al [56] reported that the variation in the IVI of species might be caused by predominant environmental factors. Moreover, the difference in IVI among the sites may be due to the composition of plant species, human activities, and local ecological factors [57].…”
Section: Discussionmentioning
confidence: 99%
“…As observed from the IVI analysis, P. austroarabica had the highest importance value (107.28) as compared with other parasitic species. Magray et al [56] reported that the variation in the IVI of species might be caused by predominant environmental factors. Moreover, the difference in IVI among the sites may be due to the composition of plant species, human activities, and local ecological factors [57].…”
Section: Discussionmentioning
confidence: 99%
“…Phyto‐ecological assessment of the medicinally important plant species is a key aspect in the field of vegetation science as well as in other scientific disciplines such as conservation, management, and bioprospecting of phytoresources (Magray et al 2022, Rashid et al 2023a). Studying natural communities is crucial for gaining insight into the species composition, the structure of communities, plant population growth and abundance, and the interactions between plants and their environment (Chawla et al 2012, Mishra et al 2012).…”
Section: Introductionmentioning
confidence: 99%
“…It leads to the proper identification of plant species and thereby conservation in a scientific and systematic way. The distribution of plant species is a valuable source of information for environmental factors and ecosystem services in a particular habitat (Angyalossy et al, 2022;Flores-Argüelles et al, 2022;Magray et al, 2022;Shannon et al, 2022;Wani et al, 2022b;Watts et al, 2022). Floristic diversity is used to interpret plant species of any geographical area, whether cultivated or wild in their nature (Farooq et al, 2019;Khan and Badshah, 2019;Ca et al, 2020;Wani et al, 2022a).…”
Section: Introductionmentioning
confidence: 99%